Addressing Supply Chain Management Issues in Cost-effective Maternal and Pediatric Global Surgery: A Call to Action - Sergio M. Navarro, MBA; Andile Sibiya, MBChB, FCORL, MBA; Maziar M. Nourian, MD; Kelsey A. Stewart, MD; Taylor D. Ottosen, BS; Raymond R. Price, MD (Global Health and Education Projects, Inc., 2019)
Persistent global disparities in maternal and neonatal outcomes exist, in part, due to a lack of access to safe surgery. This commentary examines the relative need for increased focus on access to safe maternal and pediatric surgery globally, starting with a focus on cost-effective surgeries. There is a need to understand context-specific surgeries for regions, including understanding regional versus tertiary development. Most important is a need to understand the crucial role of supply chain management (SCM) in developing better access to maternal and pediatric surgery in limited resource settings. We evaluate the role of SCM in global surgery and global health, and the current landscape of inefficiency. We outline specific findings and takeaways from recent solutions developed in pediatric and maternal surgery to address SCM inefficiencies. We then examine the applicability to other settings and look at the future. Our goal is to summarize the challenges that exist today in a global setting to provide better access to maternal and pediatric surgery and outline solutions relying on structural, SCM-related framework. Key words: • Pediatric surgery • Neonatal outcomes • Supply-chain management • Limited resource settings   Copyright © 2020 Navarro et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.